L'art avant l'art Le paradigme préhistorique - Rieber, Audrey (Tohu Bohu, 2022)
The paintings, engravings, sculptures and movable objects discovered, particularly since the discovery of Altamira, the famous decorated cave in Spain and a true masterpiece of Paleolithic art, never cease to question researchers, artists and the general public. How can we think about this 'art before art', these works of the origins to which we attribute an aesthetic value but whose realisation is prior and irreducible to the concept of art that we have today? In order to do so, we must identify the fundamental features of this prehistoric paradigm which paradoxically resonates with modern art. The treatment of gesture, figuration, space and movement will be examined as a source of inspiration and renewal for artists from Picasso to Moore. The book argues that the Paleolithic forces us to reconsider our definition of art, its functions and meanings, its beginnings and its history. The original reflections offered by specialists in philosophy, history, art history and literature will appeal to everyone who is passionate about art and its theories.